0681 Association of poor sleep with stress, anxiety, emotional support, social isolation, and depression during the COVID-19 pandemic. (25th May 2022) - Teague, Taylor; Debian, Ahmad; Kokonda, Manasa; Malhotra, Sonal; Arentson-Lantz, Emily; Shaib, Fidaa; Nowakowski, Sara
Abstract: Introduction: The COVID-19 pandemic has impacted multiple facets of daily living: personal finances, physical activity, and mental and physical health. These changes can result in additional stress and negatively affect sleep. It is important for sleep medicine providers to understand how their patients are impacted by these changes to optimize their care. In this study, we evaluated the association of poor sleep with stress, anxiety, emotional support, social isolation, and depression among sleep medicine clinic patients during the COVID-19 pandemic. Methods: Sleep medicine clinic patients were distributed an online survey at baseline followed by a 6-month follow-up survey (December 2020 - May 2021). Participants answered questions regarding Insomnia Severity Index (ISI), Patient-Reported Outcomes Measurement Information System (PROMIS) measures (sleep disturbance and sleep-related impairments), and COVID-19 testing. Stepwise linear regression was performed using SAS to determine if self-reported poor sleep predicted stress, anxiety, emotional support, social isolation, and depression. This study was approved by Baylor College of Medicine IRB. Informed consent was obtained from all subjects involved in the study. Results: Eighty-one adults completed baseline survey, and 54 adults (mean age 55.2±18.4 years, 61% female, 70% Caucasian) completed 6-month follow-up survey. At baseline, anxiety had a significant effect on sleep disturbance (0.43±0.11, p=0.0001), sleep-related impairments (0.53±0.12, p=0.0001) and ISI (0.28±0.08, p=0.0004). Upon follow-up, an increase in ISI predicted higher perceived stress (0.18±0.07, p=0.013) and worse anxiety (0.61±0.16, p=0.0003). An increase in sleep disturbance predicted a decrease in emotional support (0.25±0.12, p=0.038). Additionally, an increase in sleep-related impairments predicted an increase in social isolation (0.39±0.11, p=0.0002) and depression (0.57±0.07, p<0.0001). Interestingly, only 3 participants tested positive for COVID-19. Conclusion: In this study of sleep medicine clinic patients during the COVID-19 pandemic, we observed that poor sleep predicted greater stress, anxiety, social isolation, and depression along with less emotional support. This study illustrates the importance of addressing stress management, mental health (anxiety, depression), and emotional support when treating sleep medicine clinic patients during the COVID-19 pandemic. Support (If Any): National Institutes of Health (NIH) Grant #R01NR018342 (PI: Nowakowski); Department of Veteran Affairs, Veterans Health Administration, Office of Research and Development; Center for Innovations in Quality, Effectiveness and Safety (CIN 13-413)